STUDI TENTANG MOTIVASI BELAJAR SISWA PADA PENGGUNAAN MEDIA MOBILE GAME BASE LEARNING DALAM PEMBELAJARAN LAJU REAKSI KIMIA - Ucu Cahyana; Mario Paristiowati; Muhammad Fajar Nurhadi; Siti Nuryana Hasyrin (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Negeri Jakarta, 2017)
This study aims to analysis developing of students' learning motivation in the learning process of chemical reaction rate by using mobile game base learning media (mobile game base learning). The research was conducted at Senior High School 77 Jakarta in 2016. The method used in this research is qualitative research method. Data analysis techniques were performed with data reduction, data display, conclusions and verification. The quality standard used is trustworthiness with the criteria of credibility through prolonged engagement, persistent observation, progressive subjectivity and member checking.The results concluded that the mobile game base learning media can develop students' motivation in the aspects of relevance, attention, confidence, and satisfaction. The aspect of relevance shows a good motivation in terms of relevance of chemistry. In the attention aspect, it generates good enthusiasm and attention along becomes more interested in chemistry learning. The aspect of confidence produces good confidence for students in studying Chemistry. For the aspect of satisfaction, it produces a good sense of satisfaction. Students are also satisfied with the learning process as well as they do not feel disappointed with the learning of chemistry.